2009
DOI: 10.1152/ajpgi.90700.2008
|View full text |Cite
|
Sign up to set email alerts
|

Electrical stimulation of the mucosa evokes slow EPSPs mediated by NK1 tachykinin receptors and by P2Y1 purinoceptors in different myenteric neurons

Abstract: Gwynne RM, Bornstein JC. Electrical stimulation of the mucosa evokes slow EPSPs mediated by NK1 tachykinin receptors and by P2Y1 purinoceptors in different myenteric neurons. Am J Physiol Gastrointest Liver Physiol 297: G179 -G186, 2009. First published April 30, 2009 doi:10.1152/ajpgi.90700.2008.-Slow excitatory postsynaptic potentials (EPSPs) in enteric neurons arise from diverse sources, but which neurotransmitters mediate specific types of slow EPSPs is unclear. We investigated transmitters and receptors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 49 publications
1
21
0
Order By: Relevance
“…In the present paper, we demonstrate that ATP or a related purine acting on P2Y 1 receptor is probably the transmitter involved in this response. It is important to note that, in the presence of MRS-2500, L-NNA was still able to cause smooth muscle depolarization, suggesting that prejunctional P2Y 1 receptors that might mediate sEPSP (15) are not involved in NO release.…”
Section: Role Of P2y 1 Receptors and No On Spontaneous Ijp And Rmpmentioning
confidence: 99%
“…In the present paper, we demonstrate that ATP or a related purine acting on P2Y 1 receptor is probably the transmitter involved in this response. It is important to note that, in the presence of MRS-2500, L-NNA was still able to cause smooth muscle depolarization, suggesting that prejunctional P2Y 1 receptors that might mediate sEPSP (15) are not involved in NO release.…”
Section: Role Of P2y 1 Receptors and No On Spontaneous Ijp And Rmpmentioning
confidence: 99%
“…In the submucosal plexus, purinergic fast EPSPs are rarely observed in the small or large intestines [32,33]. Tachykinins, acetylcholine, and serotonin are the primary mediators of slow EPSPs in the ENS, but purinergic slow EPSPs mediated by P2Y 1 receptors have been reported in myenteric [34,35 ] and submucosal [32,36] ganglia. Neurotransmission from enteric and sympathetic neurons to enteric glial cells involves purinergic activation of P2Y 1 and P2Y 4 receptors [3739], and is regulated by ectonucleotidases [16,37].…”
Section: Purinergic Ganglionic Transmissionmentioning
confidence: 99%
“…In 8 cases, the axon could be followed through several ganglia before either fading or reaching the end of the preparation. In 7 of these cells, the axon produced varicose side branches in one or more ganglia (Figure 2B), indicating that it was an interneuron [12], [13]. Immunoreactivity for NOS was examined for 6 of these neurons and all were immunoreactive for this enzyme (Figure 2B).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, these slow EPSPs were found to be the result of synaptic transmission from descending interneurons with cell bodies close to the distension sensitive sensory neurons. In a second series of experiments, we showed that individual electrical stimuli applied focally to the mucosa evoked P2Y 1 mediated slow EPSPs in the same population of descending interneurons [13]. The question remains whether the slow EPSPs evoked by distension are mediated by P2Y receptors and if blocking these receptors will modify descending inhibition.…”
Section: Introductionmentioning
confidence: 94%